(untitled) (CIPEEX, 2025)
At present, Brazil faces significant challenges to its democracy from an electoral perspective, particularly concerning the exercise of women’s passive participation in elections. Only belatedly, in 1932, did women acquire the right and duty to vote, thereby gaining both active electoral capacity (the right to vote) and passive electoral capacity (the right to be elected). Drawing on a theoretical, qualitative, and comparative approach, and based on the analysis of academic studies, it becomes evident that compliance with the minimum percentage of female candidacies often serves merely a symbolic function, with women being included as token candidates to complete party slates. Law 9.504/97 established a gender quota of at least 30%. However, this measure has failed to generate the intended inclusion, due to factors such as structural machismo, lack of financial investment, and widespread fraudulent practices carried out by political parties and coalitions through the use of fictitious female candidacies. These so-called token candidacies are created solely to meet the quota requirement, producing tangible effects—for instance, in the 2024 city council elections, only 18% of those elected were women, despite women comprising more than 50% of the Brazilian electorate. It follows that the State must play a proactive role in guaranteeing, across all sectors, the necessary conditions for the effective implementation of such affirmative development policies, including the oversight and sanctioning of political parties that engage in fraudulent practices. This analysis demonstrates that gender quotas alone are insufficient to balance female representation and gender equality within the Brazilian political sphere, with profound implications for democracy.